1992
DOI: 10.2337/diacare.15.8.947
|View full text |Cite
|
Sign up to set email alerts
|

Smokers with IDDM Experience Excess Morbidity: The Colorado IDDM Registry

Abstract: OBJECTIVE--To determine whether there is an association between smoking and the self-reported morbidity of people with IDDM and to evaluate the nature of a possible interaction between smoking and IDDM in increasing the risk of morbidity among smokers with IDDM. RESEARCH DESIGN AND METHODS--Subjects were non-Hispanic whites aged 18-28 yr who participated in the Colorado IDDM Registry Follow-up Survey (case subjects, n = 24) or the 1985 NHIS (control subjects, n = 5876). Assessments of self-reported morbidity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…An increased prevalence of cardiovascular disease has been associated with BMI and WHR in type 1 diabetes [4,86]. Smoking is an independent risk factor for atherosclerosis, and type 1 diabetes and smoking interact to produce excess cardiovascular morbidity and mortality [87,88]. The age-adjusted prevalence of smoking is similar for people with or without diabetes [89,90].…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 99%
“…An increased prevalence of cardiovascular disease has been associated with BMI and WHR in type 1 diabetes [4,86]. Smoking is an independent risk factor for atherosclerosis, and type 1 diabetes and smoking interact to produce excess cardiovascular morbidity and mortality [87,88]. The age-adjusted prevalence of smoking is similar for people with or without diabetes [89,90].…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 99%
“…91 Children and adolescents with diabetes who smoke regularly are at 50% to 75% greater risk for morbidity and mortality in later life than youngsters with diabetes who do not smoke. [92][93][94] Smoking Rates Gold and Gladstein 95 reported that more than half of a sample of 79 diabetic adolescents and young adults aged 11 to 25 years reported tobacco or alcohol use at least once, and 12% to 25% reported use Ͼ5 times in their lifetime. Within their sample, white adolescents were significantly more likely to be smokers than Hispanic or black adolescents.…”
Section: Illness-and Treatment-related Complicationsmentioning
confidence: 99%
“…In addition to the deleterious effects of smoking on the mental health of individuals with diabetes, smoking is also hazardous to physical health. There is evidence that smoking is an independent risk factor for cardiovascular disease (43) and is strongly associated with higher 24-h blood pressures (44), poor glycemic control (45), increased prevalence of microvascular complications (45), diabetic nephropathy (46), and excess morbidity (47). Therefore, there is a need to discourage smoking initiation in individuals with diabetes and encourage smoking cessation in current smokers.…”
Section: Multivariate Analysesmentioning
confidence: 99%